Content Analysis and Its Application with Dynamic Online Content: A Case Study - Liauw, Toong Tjiek (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2022)
Content analysis is a well-established and widely used research method. In its early form, it was used extensively in the quantitative analysis of newspapers, and its applications later evolved to include electronic media such as radio and television. It has recently been applied to digital media, including the Internet. However, the use of content analysis in analyzing online content has been chiefly applied to static content, such as ‘static’ websites, in the early days of the Internet. Studies that involve its use in analyzing dynamic Internet content—for example, content that resides behind databases—are relatively much less common. This article is not written as a research paper per se. This article will instead discuss reflections on the efficacy of content analysis as a research method when applied to dynamic content such as DRs by using a previous study, which has applied content analysis to the dynamic content of digital repositories (DRs), as a case study. The previous study used as the basis for this article had applied content analysis to several DRs using manual counting by the researcher. In the process, several idiosyncrasies in terms of the way institutions populate their DRs with digital objects and the user metadata to facilitate discoverability of those digital objects were encountered that have introduced some ‘complication.’ This article will focus on how content analysis, as a research method, can be adapted to account for those idiosyncrasies to produce better results. This article will also identify the limitations and challenges of content analysis in dynamic online environments and offer some suggested approaches.